2001
DOI: 10.1023/a:1011035007591
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: CYP2C19 genotype dependence will be found in the anti-H. pylori therapy even when lansoprazole is used as the PPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(22 citation statements)
references
References 29 publications
1
16
2
3
Order By: Relevance
“…1,3,4) The HPLC system consisted of an LC-10AT pump, an SIL-10A auto-injector, an SPD-10A detector, a CTO-10A column oven (at 40°C), an SCL-10A system controller, and a C-R7A chromatopack (Shimadzu Co., Kyoto, Japan).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4) The HPLC system consisted of an LC-10AT pump, an SIL-10A auto-injector, an SPD-10A detector, a CTO-10A column oven (at 40°C), an SCL-10A system controller, and a C-R7A chromatopack (Shimadzu Co., Kyoto, Japan).…”
Section: )mentioning
confidence: 99%
“…A series of clinical studies on the CYP2C19 genotype and the pharmacokinetics and pharmacodynamics of three proton pump inhibitors (PPIs), omeprazole, lansoprazole and rabeprazole, were conducted to establish the individualized pharmacotherapy based on the CYP2C19 genotyping. [1][2][3][4][5] The subjects were classified into homo extensive metabolizers, hetero extensive metabolizers and poor metabolizers according to the CYP2C19 genotype diagnosed. The findings were summarized as follows: 1) plasma concentrations of omeprazole and lansoprazole after single oral administration were defined by the CYP2C19 genotype, whereas rabeprazole was not, 2) the CYP2C19 genotype-dependency of lansoprazole was weaker than omeprazole, and 3) hetero extensive metabolizers could be included with homo extensive metabolizers to be extensive metabolizers.…”
mentioning
confidence: 99%
“…16,17) An in vitro human liver microsome study indicated that the intrinsic clearance rates (V max /K m ) of the high-affinity component for heterozygous extensive metabolizers were only 2-fold lower than those for homozygous extensive metabolizers at the therapeutic concentration, and no difference in V max was found between homozygous extensive metabolizers and heterozygous extensive metabolizers. 18) In our previous studies, the pharmacokinetics of omeprazole and gastric pH after omeprazole administration in healthy subjects were well correlated with the CYP2C19 genotype, 11,12) although heterozygous extensive metabolizers can be included with homozygous extensive metabolizers as extensive metabolizers.…”
Section: Discussionmentioning
confidence: 91%
“…11,12) Briefly, 100 ml of 0.1 mg phenacetin/ml methanol (internal standard) and 2 ml of diethyl etherdichloromethane (7 : 3, v/v) were added to 0.5 ml of each plasma sample. They were extracted twice by shaking for 10 min and the mixture was centrifuged at 900ϫg for 10 min.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation